THE ROLE OF WIGO SAVINGS AS AN INNOVATIVE PRODUCT IN IMPROVING THE COMPETITIVENESS OF PT. BANK WOORI SAUDARA INDONESIA 1906 TBK - Dea Amelia, Dea; Usmar, Andi (PT. Jurnal Center Indonesia Publisher, 2026)
This study is motivated by the intensifying competition in Indonesia's banking industry amid digital transformation and growing global economic mobility. In such a context, product innovation becomes a crucial strategy to strengthen a bank's competitive position. PT Bank Woori Saudara Indonesia 1906 Tbk introduced the WiGo Savings product, specifically designed for South Korean citizens who plan to live or work in Indonesia through a pre-account opening scheme. This research aims to analyze the role of WiGo Savings in enhancing the bank's competitiveness, particularly in terms of product differentiation and the potential strengthening of low-cost funds (CASA). The study employs a qualitative descriptive approach with a case study method, using literature review and secondary data analysis from bank reports, media publications, and academic references related to banking innovation. The findings indicate that the pre-arrival account opening mechanism reduces administrative barriers, accelerates service activation, and creates early customer engagement. The product also shows the potential to increase CASA composition, leading to lower cost of funds and greater flexibility in credit pricing. Furthermore, WiGo enhances product differentiation and institutional branding as a bank responsive to cross-border transaction needs. However, its effectiveness depends on successful market education, cross-jurisdiction regulatory compliance, and technological system integration.